Fracture and toughening mechanisms in nanotwinned and nanolayered materials - Zhao, Huaizhi (2022)
Hierarchical nanotwinned and nanolayered structures, which are specially designed by introducing multiple interfaces, have exhibited superior resistance to fracture and failure. In this article, some recent advances in computational and experimental studies aimed to understand the fracture behavior and toughening mechanisms in these materials are reviewed. New stratagems on manipulating both microstructure (such as the size of nanotwin bundles) and mechanics (mainly related to loading orientation with respect to twin boundaries) to mediate the deformation and toughening modes provide promising paths to further optimize the properties of nanotwinned and nanolayered materials.